Diversity and Nature Tourism Potential of Orchids in Labis Forest Reserve (West Endau-Rompin), Johor - Rahmat, Umirul Akmalissa; Yap Jing Wei,; Mohd. Ilham Norhakim Lokman,; Salman Faris Zaharin, (Enhanced Knowledge in Sciences and Technology, 2024)
The Orchidaceae family, with its vast and diverse species, plays a significant role in global flora. Orchids, distributed mainly in tropical regions, exhibit distinctive growth patterns and adaptations to various environments. This thesis explores the taxonomy, ecological niches, and growth patterns of orchids, emphasizing their economic value and the challenges posed by over-collection. The escalating demand for orchids in the horticultural market has led to conservation concerns, particularly for vulnerable species. Orchid tourism emerges as a sustainable solution, integrating in-situ and ex-situ conservation strategies. This study focuses on Labis Forest Reserve in Endau-Rompin, Malaysia, as a potential orchid tourism destination, addressing the current lack of baseline data. The objectives include creating a species checklist, assessing orchid-based nature tourism potential, and mapping suitable areas within Labis Forest Reserve. The study scope encompasses hiking trails, waterfalls, and recreational areas, evaluating orchids based on nature tourism criteria. Significantly, this research pioneers a comprehensive survey of Labis Forest Reserve's orchid flora, contributing to updated biodiversity records and facilitating nature tourism enhancement. The methodology, emphasizing the study site's unique characteristics and the systematic collection and preparation of orchid specimens. The herbarium voucher preparation process ensures the preservation of orchid samples for subsequent analysis. Identification methods, assessment of tourism potential, and an orchid tourism survey further enrich the study's methodology, providing a holistic approach to orchid research and conservation. In conclusion, this thesis illuminates the unexplored potential of Labis Forest Reserve for orchid tourism, fostering conservation efforts and promoting sustainable engagement with natural resources. The findings contribute to global orchid knowledge, emphasizing the intersection of biodiversity conservation, economic considerations, and responsible tourism practices.